Covid-19 pandemic: help-seeking for smoking cessation among adult smokers in Malaysia during the Full Movement Control Order (FMCO) - Mohd Haazik Mohamed; Mohamad Haniki Nik Mohamed; Yessy Octavia Misdi; Chua, Bee Seok; Wanda Kiyah George Albert; Muhammad Faheem Mohd Dahlan (Kulliyyah of Medicine, International Islamic University Malaysia, 2023)
INTRODUCTION: In Malaysia, the annual death due to smoking habits recorded as more than 23 thousand yearly. Hence smoking cessation should be emphasized to reduce the annual mortality and morbidity. The purpose of this study is to identify the help-seeking behavior in smoking cessation among adult smokers and to determine its influencing factors during the Full Movement Control Order (FMCO) in Malaysia. MATERIALS AND METHOD: Data were collected from cross-sectional surveys of Malaysian adult smokers. The questionnaire was distributed online through the official social media account of the Ministry of Health Malaysia (MOHM) which commenced from 31st May 2021 in conjunction with the World No Tobacco Day. A multivariate binomial logistic regression was employed to analyze the relationship model between the predictors with the help-seeking for smoking cessation. RESULT: Out of 2,545 Malaysian adult smokers who have responded, 2,303 were males (90.5% of respondents) with mean age(sd) of 34.82(8.11) years (18 to 77 years). Slightly half (n=1353, 53%) have reported seeking help for smoking cessation and (n=1468, 57.7%) reported being unaware of the Quitline services. Factors, such as quit smoking attempt (OR; 1.844, 95% CI = 1.384-2.458), Covid-19 pandemic situation (OR; 1.841, 95% CI= 1.553-2.183), being married (OR: 1.279, 95% CI = 1.04-1.57), unaware about Quitline services (OR; 0.660, 95% CI = 0.557-0.781), non-alcohol drinkers (OR; 0.658, 95% CI = 0.473-0.916) significantly predicted the behaviour of help-seeking for smoking cessation. CONCLUSION: The results of this study would potentially support public health efforts in Malaysia in further enhancing health promotion and education programs as well as further strengthen the policy towards quit smoking issues.